Analysis of Artificial Intelligence regulations for trustworthiness - Hyesung Park; Hun-yeong Kwon (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Artificial intelligence emerged as a powerful technology using data in the 4th Industrial Revolution. As a result, artificial intelligence is currently being considered for use in many fields due to its efficiency and function. In this situation, to actively utilize artificial intelligence, society must accept artificial intelligence as a technology that can be used in the community. In other words, trustworthiness in artificial intelligence is needed within society. Currently, many countries are preparing various measures, such as policies and laws, to secure the trustworthiness of artificial intelligence. This paper analyzes acts or bills of artificial intelligence prepared in the country based on ensuring artificial intelligence trustworthiness. Through this, this paper tries to understand the characteristics of ways to secure the trustworthiness of artificial intelligence through acts for each country and to find the legal contents that can more effectively ensure trustworthiness.